How to manage Pseudomonas aeruginosa infections - Bassetti, Matteo; Vena, Antonio; Croxatto, Antony; Righi, Elda; Guery, Benoit (Drugs in Context, 2018)
Infections with have become a real concern in hospital-acquired infections, especially in critically ill and immunocompromised patients. The major problem leading to high mortality lies in the appearance of drug-resistant strains. Therefore, a vast number of approaches to develop novel anti-infectives is currently pursued. Diverse strategies range from killing (new antibiotics) to disarming (antivirulence) the pathogen. In this review, selected aspects of antimicrobial resistance and infection management will be addressed. Many studies have been performed to evaluate the risk factors for resistance and the potential consequences on mortality and attributable mortality. The review also looks at the mechanisms associated with resistance - is a pathogen presenting a large genome, and it can develop a large number of factors associated with antibiotic resistance involving almost all classes of antibiotics. Clinical approaches to patients with bacteremia, ventilator-associated pneumonia, urinary tract infections and skin soft tissue infections are discussed. Antibiotic combinations are reviewed as well as an analysis of pharmacokinetic and pharmacodynamic parameters to optimize treatment. Limitations of current therapies, the potential for alternative drugs and new therapeutic options are also discussed.